2014
DOI: 10.4103/1319-2442.134990
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence among adult patients on hemodialysis

Abstract: Medication adherence was assessed in 89 patients on hemodialysis (HD) at the King Abdul Aziz Medical City using an Arabic version of the Morisky Medication Adherence Scale (MASS-8). The results of the study revealed that 31.46% and 40.45% of the participants showed low and medium adherence, respectively, while 28.09% showed high medication adherence. Accordingly, 71.91% of the patients visiting the dialysis unit were considered medication non-adherent. While being of older age (P = 0.012), being married (P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
4
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 23 publications
7
22
4
5
Order By: Relevance
“…This same association was observed in other studies addressing adherence to different aspects of the treatment (Alkatheri et al, 2014;Dantas et al, 2013;Sgnaolin, Prado & Figueiredo, 2012).…”
Section: Demographic Characteristicssupporting
confidence: 73%
See 1 more Smart Citation
“…This same association was observed in other studies addressing adherence to different aspects of the treatment (Alkatheri et al, 2014;Dantas et al, 2013;Sgnaolin, Prado & Figueiredo, 2012).…”
Section: Demographic Characteristicssupporting
confidence: 73%
“…Additionally, due to the high complexity of the treatment, most studies focus on the analysis of one of the treatment aspects (i.e., adherence to medication, or to fluid or diet restrictions), which hinders the establishment of general conclusions (Schmid et al, 2009;Martins et al, 2013;Alkatheri et al, 2014). This study's aim was to assess adherence to different aspects of the HD treatment of ESRD patients and identify the relationship between adherence to treatment and sociodemographic and psychological variables.…”
Section: Adherence To Hemodialysismentioning
confidence: 99%
“…Many other published studies reported lack of diet and medication adherence among patients undergoing HD [17–21]. Despite the importance of adherence in general population of patients and in HD patients in particular, there are very limited number of studies which discussed this topic at the local and regional level in Arab countries [2224]. In Palestine, there are few studies on medication adherence in general and none about adherence in HD patients [2533].…”
Section: Introductionmentioning
confidence: 99%
“…12 Additionally, there is a lack of local data on the prevalence and determinants of nonadherence among dialysis patients in Saudi Arabia. 20 The objective of this study was to examine the prevalence of psychological ailments including depression, anxiety, insecure attachment style, and cognitive impairment and their associations with adherence to the recommended management of ESRD among patients on maintenance dialysis.…”
Section: Introductionmentioning
confidence: 99%